Timescales of interface-coupled dissolution-precipitation reactions on carbonates - Renard, F.; Røyne, A.; Putnis, Christine (Elsevier, 2019)
In the Earth's upper crust, where aqueous fluids can circulate freely, most mineral transformations are controlled by the coupling between the dissolution of a mineral that releases chemical species into the fluid and precipitation of new minerals that contain some of the released species in their crystal structure, the coupled process being driven by a reduction of the total free-energy of the system. Such coupled dissolution-precipitation processes occur at the fluid-mineral interface where the chemical gradients are highest and heterogeneous nucleation can be promoted, therefore controlling the growth kinetics of the new minerals. Time-lapse nanoscale imaging using Atomic Force Microscopy (AFM) can monitor the whole coupled process under in situ conditions and allow identifying the time scales involved and the controlling parameters. We have performed a series of experiments on carbonate minerals (calcite, siderite, dolomite and magnesite) where dissolution of the carbonate and precipitation of a new mineral was imaged and followed through time. In the presence of various species in the reacting fluid (e. g. antimony, selenium, arsenic, phosphate), the calcium released during calcite dissolution binds with these species to form new minerals that sequester these hazardous species in the form of a stable solid phase. For siderite, the coupling involves the release of Fe 2+ ions that subsequently become oxidized and then precipitate in the form of Fe III oxyhydroxides. For dolomite and magnesite, dissolution in the presence of pure water (undersaturated with any possible phase) results in the immediate precipitation of hydrated Mg-carbonate phases. In all these systems, dissolution and precipitation are coupled and occur directly in a boundary layer at the carbonate surface. Scaling arguments demonstrate that the thickness of this boundary layer is controlled by the rate of carbonate dissolution, the equilibrium concentration of the precipitates and the kinetics of diffusion of species in a boundary layer. From these parameters a characteristic time scale and a characteristic length scale of the boundary layer can be derived. This boundary layer grows with time and never reaches a steady state thickness as long as dissolution of the carbonate is faster than precipitation of the new mineral. At ambient temperature, the surface reactions of these dissolving carbonates occur on time-scales of the order of seconds to minutes, indicating the rapid surface rearrangement of carbonates in the presence of aqueous fluids. As a consequence, many carbonate-fluid reactions in low temperature environments are controlled by local t hermodynamic equilibria rather than by the global equilibrium in the whole system.